The Mode of Action of Spatial Repellents and Their Impact on Vectorial Capacity of Anopheles gambiae sensu stricto - Ogoma, Sheila B. (Public Library of Science, 2014)

(untitled) (PLoS One)
Malaria vector control relies on toxicity of insecticides used in long lasting insecticide treated nets and indoor residual spraying. This is despite evidence that sub–lethal insecticides reduce human–vector contact and malaria transmission. The impact of sub–lethal insecticides on host seeking and blood feeding of mosquitoes was measured. Taxis boxes distinguished between repellency and attraction inhibition of mosquitoes by measuring response of mosquitoes towards or away from Transfluthrin coils and humans. Protective effective distance of coils and long-term effects on blood feeding were measured in the semi–field tunnel and in a Peet Grady chamber. Laboratory reared pyrethroid susceptible Anopheles gambiae sensu stricto mosquitoes were used. In the taxis boxes, a higher proportion of mosquitoes (67%–82%) were activated and flew towards the human in the presence of Transfluthrin coils. Coils did not hinder attraction of mosquitoes to the human. In the semi–field Tunnel, coils placed 0.3 m from the human reduced feeding by 86% (95% CI [0.66; 0.95]) when used as a “bubble” compared to 65% (95% CI [0.51; 0.76]) when used as a “point source”. Mosquitoes exposed to coils inside a Peet Grady chamber were delayed from feeding normally for 12 hours but there was no effect on free flying and caged mosquitoes exposed in the semi–field tunnel. These findings indicate that airborne pyrethroids minimize human–vector contact through reduced and delayed blood feeding. This information is useful for the development of target product profiles of spatial repellent products that can be used to complement mainstream malaria vector control tools.